Separating altermagnetic and ferromagnetic effects in X-ray magnetic dichroism of rutile NiF2 - A. Hariki; K. Sakurai; T. Okauchi; J. Kuneš (npj Quantum Materials)
Abstract We present numerical simulations of X-ray magnetic circular dichroism (XMCD) at the L 2,3 edge of Ni in the weakly ferromagnetic altermagnet NiF2. Our results predict a significant XMCD signal for light propagating perpendicular to the magnetic moments, which are approximately aligned along the [010] easy-axis direction. The analysis shows that the altermagnetic and ferromagnetic contributions to the XMCD signal can be uniquely distinguished by their dependence on an applied magnetic field. By varying the angle of the field relative to the easy axis, the in-plane orientation of both the Néel vector and the net magnetization can be systematically controlled. We further demonstrate that the XMCD signal, even under fields as strong as 40 T and for any in-plane orientation, can be accurately described as a linear combination of two spectral components, with geometrical prefactors determined by the field’s magnitude and direction. This insight enables experimental validation of the distinctive relationship between the Néel vector orientation and the X-ray Hall vector in the rutile structure. Quantitative simulations supporting these findings are provided.